2015
DOI: 10.1007/s10853-015-9044-7
|View full text |Cite
|
Sign up to set email alerts
|

Elastic consideration of the precipitation in model alloys of maraging steels: theory and experimental validation

Abstract: The unique combination of high strength and high fracture toughness in maraging steels is attributed to the precipitation of mainly two phases, Ni 3 Mo and Ni 3 Ti, in the soft bcc martensitic matrix. Experimentally, it is difficult to distinguish between these phases; moreover, the effect of each precipitating phase on the properties of the steel is ambiguous. In the present work, we tackle these questions by analyzing the elastic fields and elastic energy associated with each precipitating phase and their ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…Since Fe-Mo precipitates are not coherent with the matrix, contrary to Ni 3 Mo and Ni 3 Ti, its formation barrier is much higher. It was calculated in [32] that the elastic energy in the matrix surrounding a Ni 3 Mo precipitate is two orders of magnitude lower than in the vicinity of the Ni 3 Ti precipitate, implying that the formation barrier of Ni 3 Mo is low. Thus, although unstable, Ni 3 Mo precipitate forms at the early stages of aging along with the stable Ni 3 Ti phase.…”
Section: Discussionmentioning
confidence: 99%
“…Since Fe-Mo precipitates are not coherent with the matrix, contrary to Ni 3 Mo and Ni 3 Ti, its formation barrier is much higher. It was calculated in [32] that the elastic energy in the matrix surrounding a Ni 3 Mo precipitate is two orders of magnitude lower than in the vicinity of the Ni 3 Ti precipitate, implying that the formation barrier of Ni 3 Mo is low. Thus, although unstable, Ni 3 Mo precipitate forms at the early stages of aging along with the stable Ni 3 Ti phase.…”
Section: Discussionmentioning
confidence: 99%
“…(Received on September 26, 2018; accepted on January 16,2019) The present work has studied the kinetics of partial reversion of martensite into austenite, which occurred during overaging between 520 and 600°C in a maraging 350 steel. The microstructural modifications were followed using optical microscopy, scanning electron microscopy, X-ray diffraction and ferritoscopy.…”
Section: Kinetics Of Martensite Reversion To Austenite During Overagimentioning
confidence: 99%
“…and would be used in the formation of the austenite reversion and the molybdenum used in the formation of the Fe 2 Mo. 1,6,11,13,14) Studies performed by Moshka and coauthors 15) and by Shmulevitsh and coauthors 16) showed that the Ni 3 Mo precipitate is thermodynamically more unstable than the Ni 3 Ti precipitate. In this way, it is more probable that the dissolution of the Ni 3 Mo precipitate may give origin to the reverted austenite and to the Fe-Mo precipitates simultaneously.…”
Section: Kinetics Of Martensite Reversion To Austenite During Overagimentioning
confidence: 99%
“…Maraging steel is a typical high-strength steel, which has been taken as significant material options for the production of rocket engines, aircraft, cryogenic missiles, deep manned cabin, etc. [1][2][3][4][5][6] . In addition to the tensile properties, the fatigue properties of maraging steel are also the significant factors influencing its industry application.…”
Section: Introductionmentioning
confidence: 99%